Factors Affecting Auditors Decisions to Change Profession - Vaicekauskas, Darius (Buhalterinės apskaitos teorija ir praktika, 2023)
The cornerstone of audit business is human resources – people, their knowledge and skills create the greatest added value in the provision of audit services. It is noticeable that recently audit companies have been facing serious human resource management challenges - it is becoming more difficult to motivate employees to continue their career in the audit business.The article examines what factors affect the decision of Lithuanian auditors to change their profession and leave the audit business. It was determined that the decision of auditors to leave the profession is affected by various factors, which can be grouped into 4 groups: (1) the image of the profession, (2) the environment of the profession, (3) the working environment and (4) the factors of working conditions. The following working conditions and work environment factors were determined to be of highest importance: (1) excessively long working hours, (2) excessive workload, (3) inability to balance work and free time, (4) uncompetitive salary. The research results show that the factors determining the auditors' decision to leave the profession do not differ significantly, regardless of the time when the auditors left the profession. However, it should be noted that auditors who left the profession in later years were more influenced by dissatisfaction with the factors of working conditions (workload, working hours, balancing work and free time, uncompetitive salary). This indicates that in recent years, with the growth of the Lithuanian economy and in general, more availability of different opportunities to pursue a career in various directions, the younger generation of auditors perceive and accept the complexity of audit work and the remuneration for it differently and choose other, more attractive work alternatives.
Keywords: audit; auditors; factors; employee turnover; profession